Design and thermal conductivity of 3D artificial cross-linked random fiber networks. (August 2022) - Kallel, Houssem; Joulain, Karl
Graphical abstract: Highlights: Steps to creating a 3D model of a cross-linked Random Fiber Network (RFN) are given. FEM is used to study the heat conduction in a cross-linked RFN and compute its ETC. The ETC of a glass RFN depends strongly on the orientation and fraction of fibers. The ETC of a glass RFN is related most directly to the percolation paths through it. Abstract: We propose a novel procedure to design three-dimensional (3D) printable cross-linked random fiber networks. Our procedure describes how to implement, in a novel way, a modified version of random-walk based algorithm using a combination of different free and open-source software programs. Second, we describe in detail a method based on an open-source finite-element software, to analyse the steady-state heat conduction and to compute the effective thermal conductivity for cross-linked fibrous structures immersed in vacuum. We apply this method to examine how the orientations of the fibers and the fiber volume fraction influence the effective thermal conductivity of 3D artificial cross-linked random glass fiber networks. Our numerical results show explicitly the direct link between the effective thermal conductivity and the percolating conduction paths through a 3D cross-linked fiber network. The proposed procedure for creating the 3D drawing and the one for volume meshing as well as the method for solving the steady-state heat conduction problem described in this paper can be extended to other 3D complex structures with closed surfaces.